Nanoscale modulation of electronic states across unit cell steps on the surface of an epitaxial colossal magnetoresistance manganite film - Rana, Abhimanyu; Bogle, Kashinath A.; Game, Onkar S.; Patil, Shankar; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2010)
The nature of electronic states near the edge of unit cell steps on the surface of epitaxial La(0.7)Sr(0.3)MnO(3) (LSMO) thin films grown by real-time reflection high energy electron diffraction monitored pulsed laser deposition is examined by scanning tunneling microscopy and scanning tunneling spectroscopy techniques. It is observed that the electronic states are strongly modulated near the step edge with considerably high gap at the edge and low gap on the terrace. This modulation weakens at low temperature. The temperature evolution of the density of states and the nature of gap in deep metallic state of LSMO are also discussed. (C) 2010 American Institute of Physics. [doi:10.1063/1.3455886]
Keywords: colossal magnetoresistance; electronic density of states; lanthanum compounds; magnetic epitaxial layers; Nanostructured materials; pulsed laser deposition; reflection high energy electron diffraction; scanning tunnelling microscopy; scanning tunnelling spectroscopy; strontium compounds